DUKUNGAN PEMERINTAH DAN MASYARAKAT TERHADAP KERJA SOWOHI SEBAGAI PEMIMPIN INFORMAL DI KAMPUNG ADAT KALAODI, KOTA TIDORE KEPULAUAN - Abdurrahman Kader; Abubakar Muhammad Nur; Dahlan Husain (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2020)
Informal leaders have a significant role in the social life of the community. In carrying out their role, informal leaders need support from the community and formal leaders. The main objective of this research is to examine government and community support for Sowohi work as an informal leader in indigenous peoples in Kalaodi Village, Tidore Archipelago City. The method used is qualitative with a descriptive approach, and data sources obtained from interviews, documents, and observations. The data analysis technique used is an interactive model. The results of the study explained that the government and community support for Sowohi as the informa leader in the Kalaodi indigenous people was very large. Support from the government, such as the administration of permits and the cost of traditional rituals. Meanwhile, the support from the community is in the form of manpower, expenses, and food assistance.